On Teaching Logic and Algebraic Specification - Mossakowski, Till (Electronic Communications of the EASST, 2010)
We discuss teaching experiences with courses on first-order logic andon algebraic specification, with an emphasis on software tools that can be used by students and that illustrate the meaning of logical notions. In particular, we discuss Language, Proof and Logic and the Heterogeneous Tool Set. Moreover, we claim that structuring constructs like those of the Common Algebraic Specification Language can be better digested when starting with applying them to propositional logic.